Taxation, infrastructure investment, growth, and poverty reduction: A case study of Zimbabwe - Hans Lofgren; Martín Cicowiez (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2022)
In recent decades, Zimbabwe's development record has been disappointing. In the last few years, a severe drought and the Covid-19 pandemic have added to the country's development challenges. This paper is concerned with the long-run need to find a path toward faster growth in GDP, employment, and incomes, accompanied by more rapid progress on poverty reduction and other parts of the global sustainable development agenda. As part of this search, the country will need to address structural constraints including a large infrastructure gap, an inefficient government, and unhospitable business climate. Among these, this paper is focused on infrastructure and alternative means of financing scaled-up investments - what are the consequences of relying on domestic taxes compared to foreign financing? To address these questions, the paper draws on simulations with SDGSIM, a computable general equilibrium (CGE) model, designed for SDG analysis but applicable to analysis of policies in a wide range of areas, including growth, fiscal space, and external shocks. The model was adapted to the Zimbabwean context and calibrated to a database for 2016. The simulations cover the period 2016-2030 and analyzes the effects of alternative levels and priorities for government spending and resource mobilization (domestic and foreign). The simulation results cover a wide range of economic indicators, including some related to the global Sustainable Development Goal (SDG) agenda. [...]
Keywords: C68; H54; O55; 330; infrastructure investment; economic growth; poverty alleviation; private consumption; taxation procedures; scenario technique; Zimbabwe; Infrastrukturinvestition; Wirtschaftswachstum; Armutsbekämpfung; Privater Konsum; Besteuerungsverfahren; Szenariotechnik; Simbabwe